Guerra às drogas na cidade: práticas de estado na construção de territórios de exclusão - Guilherme Roedel Fernandez Silva (2022)
It is not possible to specify when human relations with drugs began. They probably go back to the beginnings. The prohibition, however, is much more recent. The history of prohibitionism reveals that the concern with possible health risks caused by the abusive consumption of drugs is secondary in relation to the political, economic and ideological interests that sustain the War on Drugs. In Brazil, the prohibition of marijuana is contemporary with the criminalization of capoeira and curandeirismo, traditional practices of peoples of African origin. Criminalizing customs and traditions of African peoples was one of the mechanisms used to maintain social control over the black population freed from enslavement. The industrial revolution created an economic atmosphere that suffocated the slave regime. The evolution of chemistry, the strengthening of the pharmaceutical industries and the World Wars converged to regulate the international drug market, criminalizing certain substances. The expansion of industrialization highlighted the centrality of cities, attracting services, products, wealth and people to urban space. The unequal distribution of wealth and opportunities in cities is reflected in the unequal access to the occupation and use of urban land. Excluded from access to land, education and work with decent wages, vulnerable groups that migrated to the cities in search of opportunities were forced to cluster in marginal lands, without adequate infrastructure, giving rise to the phenomenon of slums and fragmenting the urban sociospatial fabric. Difficulties in supporting themselves and their families, as strong as the desires for consumption stimulated by capitalism, contribute to making the lucrative and dangerous trade in illegal drugs an alternative for young people living in the favelas. The capture of favelas by traffickers reinforces the original label of unhealthy and dangerous territories, attracting repressive policing. The research analyzed all occurrences of drug trafficking and use in Montes Claros in the year 2021, with the aim of identifying how State practices have materialized in the context of the war on drugs in the city. The characteristics of the assessed population and the socioeconomic conditions of the urban territories where such acts occur were identified, in order to identify differentials in the treatment given by State agents to those approached due to the place of approach or the socioeconomic condition of the assessed person. It was found that although the consumption and sale of drugs are widespread among different social groups throughout the city, state practices to confront it are rigorously concentrated in the retail trade carried out by young people with low education in the favelas and their surroundings. In search of drugs, the police carry out random searches of people, interrogate suspects without warning of the right to silence and invade homes without a warrant, contrary to the jurisprudence of the Superior Courts that reinforces the effectiveness of fundamental individual rights against arbitrary attacks by the State. Informal investigations based on anonymous informants impede external control of police activity and facilitate the distortion of democratic practices. The work concludes that the over-policing of these territories and the daily arrest of young people involved with drugs, in addition to not affecting supply and consumption, generates a vicious circle that goes through the classification of these territories as Hot Zones of Crime and reinforces the marginalization of the inhabitants of the shanty towns. State practices in the war on drugs in the city contribute to the construction of territories of exclusion.